ANALISIS KINERJA RANTAI PASOK PEMBUDIDAYA IKAN LELE DI KEDIRI STUDI KASUS PADA PEMBENIHAN DAN PEMBESARAN - Nurkhasanah, Anissa Aprilia; Mazaya, Amalia Febryane Adhani; Maulidiyah, Vika; Hadiana, Hadiana; Cahya, Nur Evana Inge Dwi; Septrisia, Sheila (Torani Journal of Fisheries and Marine Science, 2025)
This study aims to analyze the supply chain system in catfish farming in Kediri, focusing on three main aspects: the flow of goods, financial flow, and information flow. It also aims to identify the actors involved in the supply chain and determine the appropriate supply chain model. This research was conducted from March to July 2025 among four catfish farmers in Kediri city and regency. The method used is a case study approach with interviews with four business actors consisting of catfish breeders and growers. The data analysis used exploratory descriptive analysis, explaining the actors involved in the supply chain, the flow of goods, the flow of money, and the flow of information in the form of graphs, tables, and figures. The results show that the flow of goods is dominated by an informal distribution network through middlemen, with distribution patterns varying between business actors depending on the type of business. With minimal intervention from the credit system and a high degree of trust between actors, financial flow occurs easily through cash and transfer channels.  Without written contracts, information is communicated directly between people, making it less formal yet more flexible.  The resulting supply chain model is a trust-based supply chain in which players cooperation is primarily driven by their social relationships.  In order to increase the effectiveness, sustainability, and transparency of the supply chain for catfish farming in Kediri, this study suggests that institutional assistance and technology integration are necessary.